Abnormal muscle tension as one of the main problems after a stroke - Zaborna, Daria; Lazarek, Maciej; Husejko, Jakub; Lamch, Magdalena; Belczyńska, Magdalena; Kontowicz, Marlena; Cięszka, Karolina; Kubiak, Karolina; Krakowska, Natalia; Zwolinski, Adrian; et al. (Journal of Education, Health and Sport, 2019)
Background: Stroke is a growing problem in an aging society. According to WHO data, it is the second most common cause of death. An increase in the number of strokes causes an increase in the number of patients struggling with its consequences. People who have suffered a stroke are dealing with various neurological defects. One of them is abnormal muscle tension. Material and methods: Analysis of available literature, articles in the Google Scholar and PubMed database using keywords: stroke, muscle tension, spasticity. Results: The problem of disturbed tension is common in people who have had a stroke. Spasticity, i.e. increased muscle tone in response to stretching, results from damage to the central nervous system. Direct and indirect methods are used to assess spasticity. In the fight against destroyed muscle tension, it is important to implement treatment as soon as possible. It is based on the use of various forms of therapy: pharmacotherapy and physiotherapy. Physiotherapy and kinesitherapy treatments as well as specialized rehabilitation methods, such as PNF. The rehabilitation process should be supplemented with appropriate pharmacological treatment. Equally important is the implementation of stroke prevention. These activities are associated with the promotion of a healthy lifestyle, for example, regular exercise and stress reduction. Conclusion: Muscle tension disorder, including spasticity, is a problem affecting many patients who have had a stroke. A timely diagnosis is important to get the right therapy. Treatment should have a holistic dimension and combine different methods. The goal of therapy is to normalize muscle tone and thus improve the patient’s quality of life.